DEVELOPMENT AND PERFORMANCE EVALUATION OF A KEROSINE FUELED INCUBATOR - AJAYI, O. A; OSUNBITAN , J. A; ASAOLU, O. A (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The price of day old chicks has recently skyrocketed in the Nigerian poultry market. This is mainly due to the scarcity of materials for producing day old chicks, a problem resulting from the prohibitive cost of imported incubators. Design and construction of a locally made incubator if proved functional wilt save a lot of foreign exchange. The availability of a locally built incubator will be an advantage to farmers. In as much as the machine will be simple in construction, its operation will not be difficult for the average farmer. This paper reported design and operation of an incubator which uses kerosine as a source of heat. The control .of temperature and relative humidity is done manually. Temperature is controlled by varying the size of the air inlet/ gate at the sides of the incubator. Humidity is however varied by varying the sizes of water tray placed at the base of the incubator. The turning of the eggs for the first eighteen days was carried out semi-automaticity. The observed temperature during the test period ranges between 37oC and 40.5oC and the relative humidity between 50% and 60% for the first eighteen days after which it was increased to 77% for the last three days. At the end of the incubation period, five strong chicks emerged out of their shells, four fully developed chicks unable to hatch following pipping and two dead 'germ' showing percent hatchability of the machine to be 47%.